تشفير النصوص باستخدام مفاتيح OTP من تسلسلات DNA مولدة عشوائياً - كندة أبو قاسم; تيسير سلمان (Tishreen University, 2019)
Cryptographic keys is one of the main issues when designing symmetric encryption algorithms. Several encryption algorithms have used Pseudo Random Number Generators (PRNG). The problem with PRNGs is that they are deterministic where usage of the randomly generated key will be repeated and it's occurrence depends on its length since the generation of the key is done based on mathematical mechanism or by using sources of randomness like thermal or chemical sources. The randomness property of DNA introduces a solution for the problem of key generation, which results from random succession of DNA nucleotides. Besides, DNA offers keys with lengths as required. Real DNA sequences, taken from public genetic databases exploited as a source for encryption keys. This paper demonstrates the use of OTP encryption key extracted from random generated DNA sequences as a substitute for DNA sequences taken from public genetic databases and performance evaluation of the proposed algorithm by applying the algorithm on text files of different sizes.   يعتبر توليد مفاتيح التشفير أحد المسائل الأساسية في تصميم خوارزميات التشفير المتناظر. تم استخدام مولدات الأرقام العشوائية PRNG من قبل العديد من خوارزميات التشفير. تكمن مشكلة مولدات الأرقام العشوائية بأنها تتصف بالحتمية أي أن المفتاح المولد عشوائياً سوف يتكرر، وحدوث التكرار يحدده طول مفتاح التشفير، لان التوليد يتم بناءً على آلية رياضية أو يمكن استخدام مصادر للعشوائية مثل مصادر حرارية أو كيميائية. تقدم العشوائية الكبيرة DNA حلاً لمشكلة توليد المفاتيح والتي تنتج من التتالي العشوائي لأسس DNA أو النيكليوتيدات؛ كذلك يقدم مفاتيح بأطوال حسب المطلوب. تم استخدام تسلسلات DNA حقيقية مأخوذة من قواعد بيانات جينية عامة كمصدر للحصول على مفاتيح التشفير. تقدم هذه الورقة كيفية استخدام مفاتيح تشفير OTP مستخلصة من تسلسلات DNA تم توليدها عشوائياً وذلك كبديل عن تسلسلات DNA المأخوذة من قواعد البيانات الجينية العامة وتقييم الأداء لخوارزمية التشفير المستخدمة من خلال تطبيق الخوارزمية على ملفات نصية بحجوم مختلفة.